Design framework for multifunctional additive manufacturing: placement and routing of three-dimensional printed circuit volumes - Panesar, Ajit; Brackett, D.; Ashcroft, Ian; Wildman, Ricky D.; Hague, Richard J.M. (ASME, 2015)
A framework for the design of additively manufactured (AM) multimaterial parts with embedded functional systems is presented (e.g., structure with electronic/electrical components and associated conductive paths). Two of the key strands of this proposed framework are placement and routing strategies, which consist of techniques to exploit the true-3D design freedoms of multifunctional AM (MFAM) to create 3D printed circuit volumes (PCVs). Example test cases are presented, which demonstrate the appropriateness and effectiveness of the proposed techniques. The aim of the proposed design framework is to enable exploitation of the rapidly developing capabilities of multimaterial AM.